2004
DOI: 10.2176/nmc.44.14
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Two Possible Compression Sites of the Deep Branch of the Radial Nerve and Nerve Supply of the Extensor Carpi Radialis Brevis Muscle

Abstract: The posterior interosseous nerve arises from the deep branch of the radial nerve, and compression by adjacent structures results in posterior interosseous nerve syndrome. Sixty upper limbs from 30 Turkish subjects (18 males and 12 females) were dissected to reveal the course of the posterior interosseous nerve and to examine possible compression sites at the proximal and distal edges of the supinator muscle, and the exit of the nerve from the extensor carpi radialis brevis muscle. Posterior interosseous nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…There are 3 types of radial neuropathy, according to the level of injury : PIN palsy, SRN palsy, and combined6,8,9,10). The PIN is most vulnerable to entrapment just beyond its origin as it passes beneath the arcade of Frohse at the proximal edge of the supinator in the radial tunnel9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are 3 types of radial neuropathy, according to the level of injury : PIN palsy, SRN palsy, and combined6,8,9,10). The PIN is most vulnerable to entrapment just beyond its origin as it passes beneath the arcade of Frohse at the proximal edge of the supinator in the radial tunnel9).…”
Section: Discussionmentioning
confidence: 99%
“…The PIN is most vulnerable to entrapment just beyond its origin as it passes beneath the arcade of Frohse at the proximal edge of the supinator in the radial tunnel9). Compression of the PIN alone may manifest as pure motor weakness in its distribution, resulting in the inability to extend the metacarpophalangeal joints of the finger and thumb, as well as weakness in extending the thumb at the interphalangeal joint, which is also called "finger drop."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty upper limbs from 30 Turkish subjects (18 males and 12 females) were dissected to reveal the course of the PIN and to examine possible compression sites at the proximal and distal edges of the supinator muscle, and the exit of the nerve from the ECRB (Kirici & Irmak, 2004). An anatomic study of 45 supper limbs, from 40 cadavers, was performed to analyse the relations between the medial edge of the ECRB and the PIN and Laulan et al (1994) suggested that the ECRB is a possible cause of PIN entrapment.…”
Section: Discussionmentioning
confidence: 99%
“…La Arcada de Frohse es el lugar más frecuente de compresión del radial - 12,23,27,[29][30][31][32][33][34][35][36] .…”
Section: Conclusionesunclassified